PSICOGENESIS DE LOS SINTOMAS CORPORALES - GONZALEZ ENRIQUEZ, RAUL (Departamento de Salud Pública, CD MEXICO, DF, MEX, 1975)
Basic notions supporting the psychogenic theory of bodily ailments are reviewed: (1) affective equivalents; (2) expression of unconscious effects by way of hormonal chemical changes; (3) physical results of unconscious activities such as habits imposed by
J BRAS PSIQUIATR
Keywords: PSICOGENESIS, SINTOMAS CORPORALES; CIENCIAS MEDICAS; PSIQUIATRIA; PSIQUIATRIA GENERAL